MENINGKATKAN PRESTASI BELAJAR SISWA PADA PELAJARAN PLANTAE MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING - Asfarneli, Asfarneli; yusup, iwan ridwan (Jurnal BIOEDUIN, 2018)
The purpose of this study is to know the improvement of learning outcomes X grade MIA 5 student on basic biology in Plantae basic competence using Discovery Learning model in MAN 2 Bandung. The method used in this research was classroom action research (PTK). Conducted for 2 cycles. Each cycle was done in 2 times meeting. Data collection techniques used was observation and tests. The data analysis technique takes the description of teacher and student learning activities during the action using the Discovery Learning model, then calculated the number and average, as well as for the learning outcomes calculated the number of complete and unfinished students following percentage. From the results obtained that the use of discovery learning model can improve student learning outcomes in XMIA class 5 on Biology lessons of basic competence Plantae in MAN 2 Bandung. Evidenced by increasing student learning outcomes after action (cycle I and cycle II). The high learning outcomes were accompanied by increased student learning outcomes after the action obtained from the average value, in the pre cycle obtained 56.94, increased in the first cycle to 75.44, and increased again in cycle II to 83.82. Judging from the increase ratio from the pre cycle to after the cycle I action obtained an increase of 18.5 points and after the action cycle II 8.35 points. As for the action before the cycle the action cycle II obtained an increase of 26.88 points.